Study of biomechanical properties of articular cartilage using low-field magnetic resonance imaging - Yew, Wansin (2017)
Osteoarthritis (OA) is a major health issues among the population, causing pain in the human joints. It is well recognised that the OA is mainly caused by the degeneration of articular cartilage. The earliest stage of OA resulted in the alteration of the biomechanical properties of cartilage elastic modulus and permeability. Hence, the ability to detect the disease at its earliest stage is crucial for early intervention of the disease. MRI technique is widely used to assess the condition of the articular cartilage by examining the geometrical data. However, most of the diagnoses were performed at the progressive stage of osteoarthritis. Furthermore, most of the previous works and current clinical procedures were performed using high-field MRI which require significant purchase and maintenance costs. Therefore, this study aimed to investigate the potential application of low-field MRI image in order to examine the condition of articular cartilage. Cartilage specimens obtained from the humeral head of bovine were scanned using 0.18 T MRI. It was found that the gradient echo sequence of the low-field MRI was the most suitable sequence to image the cartilage. The images of cartilage were characterised based on the intensity of the greyscale. Creep indentation test was then conducted on the cartilage specimens and subsequently the indentation test was simulated using finite element method. The biomechanical properties of cartilage elastic modulus and permeability were characterized by integrating the experimental indentation test data and computational finite element model. The average elastic modulus was found to be 0.93 ± 0.72 MPa while the permeability was 0.58 ± 0.31 ×10-15m4/Ns. Correlation analyses were performed to examine the relationship between the greyscale of MRI image and biomechanical properties of elastic modulus and permeability of the cartilage. It was found that the cartilage greyscale was moderately correlated with cartilage biphasic elastic modulus (r= 0. 513) and higher correlation was observed with the permeability (r= 0.613). Thus, present results indicate that the low-field MRI have the potential and provide promising insight to determine the condition of articular cartilage. It could be further develop to serve as an early intervention of OA disease.